(untitled) (Fiep Bulletin - online, 2015)
The present study had as purpose to provide to the Education of Youngs and Adults (EYA) students an action proposal that means to facilitate the process of teaching-learning through Physical Education classes evidencing the game. For this, the study was developed in a Municipal School that assisted EYA, where the Physical Education classes were elaborated and worked according to the schedule program of EYA. Twenty two students, male and female, participated in this study, being represented by three groups from 15 to 30 years old, from the Municipal School Henrique Ghellere in Municipal district of São Miguel do Iguaçu-Pr. The study took two months to be completed, with one hour class a week, and who participated in the research signed a voluntary participation term. A questionnaire was also applied by the end of the research for the study evaluation. The study tried to emphasize the pedagogic contents through the games so that these favored and they aided in the students’ learning in entertaining and pleasant classes. It is concluded that the Physical Education through the games can aid in the teaching-learning process in the Education of Youngs and Adults, accomplishing a work group with the teacher that alphabetizes, with recreational ludics activities seeking the learning.